2015
DOI: 10.3390/toxins7104350
|View full text |Cite
|
Sign up to set email alerts
|

Differential Adsorption of Ochratoxin A and Anthocyanins by Inactivated Yeasts and Yeast Cell Walls during Simulation of Wine Aging

Abstract: The adsorption of ochratoxin A (OTA) by yeasts is a promising approach for the decontamination of musts and wines, but some potential competitive or interactive phenomena between mycotoxin, yeast cells, and anthocyanins might modify the intensity of the phenomenon. The aim of this study was to examine OTA adsorption by two strains of Saccharomyces cerevisiae (the wild strain W13, and the commercial isolate BM45), previously inactivated by heat, and a yeast cell wall preparation. Experiments were conducted usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Differences were seen in anthocyanin adsorption capacity between the different Saccharomyces cerevisiae , some adsorbing more than twice as much as others (Morata et al, ). Meanwhile, Petruzzi et al () showed that yeast cells of Saccharomyces cerevisiae and anthocyanins have some potential for competing or interacting phenomena, and yeast cells in wine could reduce the anthocyanin content significantly, resulting in a loss of color. In addition, monomeric anthocyanins are involved in reactions initiation just after their transfer to fermenting must giving rise to new red pigments like pyranoanthocyanins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences were seen in anthocyanin adsorption capacity between the different Saccharomyces cerevisiae , some adsorbing more than twice as much as others (Morata et al, ). Meanwhile, Petruzzi et al () showed that yeast cells of Saccharomyces cerevisiae and anthocyanins have some potential for competing or interacting phenomena, and yeast cells in wine could reduce the anthocyanin content significantly, resulting in a loss of color. In addition, monomeric anthocyanins are involved in reactions initiation just after their transfer to fermenting must giving rise to new red pigments like pyranoanthocyanins.…”
Section: Resultsmentioning
confidence: 99%
“…Moreno et al (2016) believed that yeast strains could adjust the CT, keep better CI, reduce astringency, increase the depletion of oxygen, and accumulate acetaldehyde in wine. The yeast strain in wine may result in a loss of color, so it should be concerned with the selection of the best yeast strain (Petruzzi et al, 2015). The changes of CI were related to the changes of phenolic compounds such as anthocyanins in wine (He et al, 2012) and were affected by pH (Kontoudakis et al, 2011) and other factors.…”
Section: Effect Of Yeast Strains On the Color Of Mulberry Winementioning
confidence: 99%
“…Uva di Troia is a red variety and the preservation of the color is generally a desired trait. Thus, the isolates were finally studied in a laboratory medium to assess if they could negatively affect this trait, because some indigenous yeasts were reported to adsorb phenols, thus causing a color loss (Palomero and others ; Petruzzi and others ). Some isolates showed a strong interaction with grape skin (code 3), thus they could potentially cause a color loss.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, detoxification based on microbial adsorption might be a clear advantage because it can be performed by autoclaved yeast cells that cannot neither consume substrate components nor release secondary metabolites, which would lead to an alteration of organoleptic properties of the product [132]. Several inactivated yeast or their cell wall preparations have shown their ability to adsorb OTA in grape juice or wine, including strains of S. cerevisiae, S. bayanus, C. intermedia, C. fiedrichii, and L. thermotolerans [126,133,134]. Despite the good results obtained using biological decontamination, the addition of yeasts to wine needs to be controlled and a careful selection of suitable yeast should be performed.…”
Section: Control and Detoxification Methods To Reduce Ota Content In mentioning
confidence: 99%
“…Despite the good results obtained using biological decontamination, the addition of yeasts to wine needs to be controlled and a careful selection of suitable yeast should be performed. Although a high OTA adsorption ability of yeast cell walls and inactivated cells of S. cerevisiae W13 and BM45, wine treatment with these agents caused color loss of wines [134].…”
Section: Control and Detoxification Methods To Reduce Ota Content In mentioning
confidence: 99%